Coronene-containing N-heteroarenes: 13 rings in a row - Endres, Alexander H.; Schaffroth, Manuel; Paulus, Fabian; Reiß, Hilmar; Wadepohl, Hubert; Rominger, Frank; Krämer, Roland; Bunz, Uwe H. F. (Journal of the American Chemical Society, 2016)
We describe the modular synthesis of three novel large N-heteroarenes, containing 9, 11, and 13 annulated rings. This modular system features fused azaacene units to a coronene nucleus. We evaluate the optical and electronic properties and the solid-state packing of the targets. The electronic properties of the 13-ring N-heteroarene allow the fabrication of a proof-of-concept thin-film transistor. Electron mobilities up to 8 × 10-4 cm/(V s) were obtained for polycrystalline films.